حساسية ونوعية مشعرات التعداد العام والصيغة في تشخيص فقر الدم بعوز الحديد عند الأطفال قبل سن المدرسة - أصلان, سمير; رضوان, فيصل; حشيش, علا (Latakia University Journal -Medical Sciences Series, 2019)
Objective The objective of this study is to compare the laboratory parameters associated with the complete blood count CBC (mean corpuscular volume MCV , mean corpuscular hemoglobin MCH, red celldistribution width RDW ) and its role in the evaluation of iron deficiency anemia with the gold standard in diagnosis (serum iron, serum Ferritin) in terms of sensitivity and specificity , and determine positive and negative predictive values. Methods The study sample included 148 children (86 males – 62 females) of children who visited the public clinic at Tishreen University Hospital in Lattakia from January 2018 until January 2019. We excluded cases of a personal or family history of hemolytic anemia disease and iron therapy during the month prior the sample , presence of an Inflammation or current infection.Cases were excluded and blood samples were taken for CBC , serum iron and serum ferretin. Results: The lower sensitivity and specificity of MCV, MCH, and RDW compared with both serum iron and serum Ferritin in the diagnosis of iron deficiency anemia. The best of these three parameters is MCH due to the relative height of its diagnostic sensitivity to the other parameters . None of these three parameters is suitable for the results of these Study to be a diagnostic test for iron deficiency anemia. Note the high percentage of iron deficiency anemia in children of the study sample (1-6) years and was 52.70%. الهدف: تهدف هذه الدراسة إلى المقارنة بين المعالم المخبرية المرتبطة بتعداد الدم الكامل CBC (MCV حجم الكرية الوسطي, RDW معامل اختلاف حجم الكريات الحمر, MCH متوسط كتلة الهيموغلوبين في كرية الدم الحمراء) ودورها في تقييم فقر الدم بعوز الحديد وبين المعيار الذهبي في التشخيص (حديد وفيريتين المصل) من حيث الحساسية والنوعية , وتحديد القيم التنبؤية الإيجابية والسلبية. الطرق : شملت عينة الدراسة 148طفلاً (86ذكر – 62انثى ) من الأطفال المراجعين العيادة العامة في مستشفى تشرين الجامعي في اللاذقية من تاريخ كانون الثاني 2018 وحتى كانون الثاني 2019 وتم استبعاد حالات (وجود قصة شخصية أو عائلية لمرض دم انحلالي وعلاج بالحديد خلال الشهر السابق لقطف العينة , وجود قصة انتان او التهاب حالي) , وتم أخذ عينات دموية على الريق لإجراء CBC وحديد وفريتين المصل. النتائج: انخفاض حساسية ونوعية المشعرات MCV ,MCH, RDW بالمقارنة مع كل من حديد المصل وفيريتين المصل في تشخيص فقر الدم بعوز الحديد , و أفضل هذه المشعرات الثلاثة هو MCH بسبب الإرتفاع النسبي لحساسيته التشخيصية عن بقية المشعرات , إنّ أيّاً من هذه المشعرات الثلاثة لا يصلح حسب نتائج هذه الدراسة لأن يكون اختباراً مشخصاً لفقر الدم بعوز الحديد . مع ملاحظة النسبة العالية لفقر الدم بعوز الحديد عند أطفال عينة الدراسة (1-6) سنة وكانت 52.70%.